Class and racial inequalities in the criminal justice system of the United States of America - Đorđević Mila (Temida)
The subject of this paper is a theoretical consideration of the relationship between class and racial inequalities and the criminal justice system in the United States of America (USA), based on a review of relevant studies and data sources. The author concludes that the class and race of the defendant influence the outcome of criminal proceedings in the USA. They are non-normative factors that have an impact on the judge's decision-making. Within the US criminal justice system, racial and class inequalities intersect so that poor, low-educated African Americans receive the harshest treatment in the US criminal justice system. The presented research shows a milder treatment of other categories of the USA population, whose criminal acts are not perceived as too dangerous due to the social position of the perpetrator and the non-violence of those acts, as well as the absence of direct victims. Also, the author concludes that although there are more studies on the influence of race on the outcome of criminal proceedings in the USA, class shows a greater influence than race, even though the term class is rarely used in the presented research and class position is most often shown using indicators of class position.